Effects of mating disruption for codling moth, Cydia pomonella (L.) (Lepidoptera: Tortricidae), control on arthropod population and damage levels in apple orchards - Eyles, David Keith (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1998.